2022
DOI: 10.1155/2022/7496753
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Swallowing Rehabilitation Training with a Balloon Dilation Therapy on the Deglutition Function and Quality of Life of Patients with Dysphagia after Radiotherapy for Nasopharyngeal Carcinoma

Abstract: Objective. The aim of this study is to investigate the effects of swallowing rehabilitation training with a balloon dilation therapy on the deglutition function and quality of life of patients with dysphagia after radiotherapy for nasopharyngeal carcinoma (NPC). Methods. The study was a retrospective study. The data of the 100 patients with dysphagia after NPC radiotherapy in our hospital between April 2021 and April 2022 were retrospectively analyzed. The patients were separated into the control group (n = 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Previous study proposed that V60 greater than 12% of the inferior pharyngeal constrictor was significantly associated with increased rate of dysphagia which demanded enteral nutritional supporting treatment ( 26 ). Dysphagia after radiotherapy has been reported in NPC cohorts ( 27 ). Emerging studies showed that dysphagia had a significantly detrimental effect on health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study proposed that V60 greater than 12% of the inferior pharyngeal constrictor was significantly associated with increased rate of dysphagia which demanded enteral nutritional supporting treatment ( 26 ). Dysphagia after radiotherapy has been reported in NPC cohorts ( 27 ). Emerging studies showed that dysphagia had a significantly detrimental effect on health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…enteral nutritional supporting treatment (26). Dysphagia after radiotherapy has been reported in NPC cohorts (27). Emerging studies showed that dysphagia had a significantly detrimental effect on health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Its clinical manifestations are diverse, specifically manifested as a pharyngeal reflex disorder, increased difficulty in swallowing at the base of the tongue, difficulty in eating and drinking, and food outflow, which not only lead to serious damage to the patient's physical health but also a significant decline in their quality of life [11] . More seriously, patients are also at risk of inducing aspiration pneumonia, or even fatal consequences due to large pieces of food blocking the airway [12] . At this stage, conventional swallowing training measures are the mainstream treatment modality in the clinical management of post-stroke dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%